2002
DOI: 10.1034/j.1600-6143.2002.20509.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Inducible and Endothelial Nitric Oxide Synthases, Formation of Peroxynitrite and Reactive Oxygen Species in Human Chronic Renal Transplant Failure

Abstract: Nitric oxide (NO¡) is produced by NO synthases (NOS)and can interact with reactive oxygen species (ROS) to form peroxynitrite, which induces protein damage by formation of nitrotyrosine. NO¡ has a promotional effect on acute rejection. To investigate the role of NO¡ during chronic renal transplant failure (CRTF), we studied the expression of eNOS and iNOS in conjunction with H 2 O 2 production and the formation of nitrotyrosines. Nephrectomy material from 10 patients and 10 control kidneys was used in this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 25 publications
(24 reference statements)
1
49
2
Order By: Relevance
“…NO, synthesized by the iNOS is produced during ischemiareperfusion injury, has a promotional effect on acute and chronic rejection and is one of the most important suppressors of postoperative intestinal smooth muscle contractility (12,31,32). Finally, the prototypical proinflammatory cytokine IL-6 is rapidly activated after intestinal manipulation, participates in leukocyte recruitment, shows functional activity within the muscularis and has been associated with intestinal allograft rejection (33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…NO, synthesized by the iNOS is produced during ischemiareperfusion injury, has a promotional effect on acute and chronic rejection and is one of the most important suppressors of postoperative intestinal smooth muscle contractility (12,31,32). Finally, the prototypical proinflammatory cytokine IL-6 is rapidly activated after intestinal manipulation, participates in leukocyte recruitment, shows functional activity within the muscularis and has been associated with intestinal allograft rejection (33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that oxidative stress is important in the pathophysiology of chronic transplant dysfunction [6][7][8][9]. Chronic transplant dysfunction is the leading cause of a slow, but progressive decline in renal allograft function [3].…”
Section: Discussionmentioning
confidence: 99%
“…Frequently, the slow decline in graft function is not the consequence of immunological rejection, but an entity that is called chronic transplant dysfunction [3]. The exact pathophysiology is not known, but oxidative stress has been implicated [6][7][8][9]. Endogenous bilirubin is an established cytoprotectant and antioxidant [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that interstitial inducible nitric oxide synthase protein expression, nitrotyrosine, and ex vivo ROS production are increased in CAI. 44,45 The balance between the ROS production and antioxidant defenses defines the degree of OS in any given tissue. 45 Injury to the tubular epithelium causes endoplasmic reticulum (ER) stress and unfolded protein response, thereby releasing ROS leading to ischemiareperfusion injury.…”
Section: Oxidative Stressmentioning
confidence: 99%